Aplikasi Administrasi Keuangan Pondok Pesantren Berbasis Web Menggunakan Metode Scrum: Web-Based Islamic Boarding School Financial Administration Application Using the Scrum Method - Muhammad Yusuf Affandi; Farhan, Ahmad; Moh. Shohibul Wafa; Zakki Alawi (Computech : Jurnal Ilmiah Teknologi Informasi dan Komunikasi, 2023)
Darul Ulum Islamic Boarding School in providing its services, especially in the field of financial administration, still adopts a conventional approach. In this method, hostel administrators manually record the flow of money both incoming and outgoing in traditional financial books. The preparation of financial reports is also only done once every three to six months. However, there is a risk that financial data may be erased when the registrar changes jobs. Various problems arise as a result of this approach, such as errors in recording the amount of money, limited access resulting in a lack of transparency and up-to-date financial information, the possibility of data being lost or damaged due to negligence or human error, lack of supervision which makes violations difficult to track and takes a long time to detect, unavailability structured financial records making it difficult to refer to previous years' budgets, and making financial reports that take up too much time. To overcome these problems, the authors have designed and built a web-based financial administration information system for this Islamic boarding school. The approach used is the Scrum method with an Agile framework, and utilizes the Laravel framework. The programming language used is native PHP, and the database system used is MySQL.